Do Distributive Justice Really Make Public Officers Feels More Obligated in Their Job? - Djony Harijanto; Ida Bagus Agung Dharmanegara; Hafid Aditya Pradesa; Hasrudy Tanjung (Mahameru Publisher, 2022)
Social exchange theory and organizational justice theory has been seen as a standard and has become an important basis for many researches on attitudes and behavior of employees working in various organizations. This study aims to build and test a model based on the integration of these two important theories in predicting the felt obligation felt by employees working in public organizations. Public officers who work at the Agency for Personnel and Human Resources Development in Malang, East Java, Indonesia are the target population in the study. Non-probability sampling was used in this study, with 88 officers who participated in this study. By using path analysis, testing for each relationship between variables shows the results of the path coefficient. Findings suggest that even it confirms social exchange and justice theory, positive felt obligation among public employees would be more influenced with higher perceptions of distributive justice rather than perceived organizational support. Practical implications for organizations and future studies are also addressed.